Tanggung Jawab Profesi dan Kode Etik Guru - Nirwana Suciyati; Rosdiana (Jurnal Pendidikan Islam, 2025)
The paper aims to discuss and understand the concept of profesional responsibility and teachers’ code of ethics as guidelines in carrying out their duties in education. The writing is done with a descriptive approach trough literatur review from various sources such as book and journals. The resulth show that teachers’ responsibilities include moral and professional obligations in teaching, guiding, and educating students in accordance with specified standards. Teachers have various aspect of responsibilities that include improving profesionalism, responsibilities that include improving profesionalism, social responsibility, and efforts to create a positive and inclusive learning environment. Meanwhile, the teacher code of ethics serves as an ethical guideline to avoid irregularities, ensure profesionalism, and improve the quality of education. The code plays a role in supproting teacher self-reflection, raising moral standards and professionalism, and building a positive reputations as an educator with integrity. This paper concludes that implementating a code of ethics and understanding profesional responsibilities are important foundations in helping teachers perform their duties effectivey, build a conducive learning environment and achieve the goal of quality education.